Bone Marrow Metastasis as an Initial Manifestation of Gastric Carcinoma: A Rare Case Report - Milan Tripathy; Prita Pradhan; Ranjita Panigrahi; Shivam .; Shubham Jainwar; Bangam Rajendra Prasad Rao (JOURNAL OF CLINICAL AND DIAGNOSTIC RESEARCH, 2026)
Gastric adenocarcinomas, despite being a leading contributor of cancer-related mortality, presentation directly with Bone Marrow (BM) infiltration sans prior Gastrointestinal (GI) symptoms holds sparse documentation in existing literature. Though a rare phenomenon, BM studies play a pivotal role in the presentation and management of such cases. This case report describes a 36-year-old female with worsening generalised body pain accompanied by fever. Radiologic evaluation revealed multiple lytic lucencies in the vertebral bodies and pelvic bones. A subsequent BM aspiration yielded suspicious looking cells in clusters and BM biopsy suggestive of metastatic deposits. These findings prompted a workup for unknown primary malignancy. Immunohistochemistry (IHC) on trephine BM biopsy suggested a tumour that is CK7+, CK20-, CDX2-, TTF1-, ER – and CA125-; suggesting upper GI primary. A Positron Emission Tomography-Computed Tomography (PET-CT) and upper GI endoscopy revealed a mass in the proximal part of body of stomach which showed a poorly differentiated adenocarcinoma. Thus, a final diagnosis of gastric carcinoma with bone marrow metastasis was confirmed and the patient was planned for palliative care.